2016
DOI: 10.3892/ol.2016.5305
|View full text |Cite
|
Sign up to set email alerts
|

PBX3 promotes gastric cancer invasion and metastasis by inducing epithelial-mesenchymal transition

Abstract: The overexpression of pre-leukemia transcription factor 3 (PBX3) in tumors plays an important role in invasion, metastasis and proliferation in a variety of human cancer types. Tumor metastasis and angiogenesis significantly contribute to the progression of cancer and create challenges for cancer therapy. In the present study, reverse transcription-polymerase chain reaction demonstrated that PBX3 was upregulated in gastric cancer (GC) tissues and Transwell assay revealed that the overexpression of PBX3 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…However, because PBX3 depletion had no significant effects on vimentin expression, we suggest that only certain aspects of EMT depend on PBX3. Nevertheless, considering recent findings that PBX3 induces EMT in gastric cancer cells (15,43), this indicates that it may generally be involved in EMT regulation in gastrointestinal cancers. Because PBX3 also has been shown to increase migration and invasion of colon cancer cells (14) both of which are features of EMT, this further supports the notion that PBX3 directly contributes to the infiltrative phenotype of colon cancer cells at the leading tumor edge.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, because PBX3 depletion had no significant effects on vimentin expression, we suggest that only certain aspects of EMT depend on PBX3. Nevertheless, considering recent findings that PBX3 induces EMT in gastric cancer cells (15,43), this indicates that it may generally be involved in EMT regulation in gastrointestinal cancers. Because PBX3 also has been shown to increase migration and invasion of colon cancer cells (14) both of which are features of EMT, this further supports the notion that PBX3 directly contributes to the infiltrative phenotype of colon cancer cells at the leading tumor edge.…”
Section: Discussionmentioning
confidence: 95%
“…colon cancer (12)(13)(14). In gastric cancer, PBX3 has been shown to induce an infiltrative tumor cell phenotype with upregulation of vimentin and repression of E-cadherin (15). In addition, microRNAs that were shown to regulate PBX3 included members of the miR-200 family (16).…”
mentioning
confidence: 99%
“…The seven GRGPs consisted of 12 genes, among which two genes (CES1 and TNFRSF11A) were also part of the 11‐Gene signature. Of these 12 genes, only PBX1 has been investigated for potential mechanism in GC . We thought the other 11 genes might also play a role in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have indicated a role for PBX3 in promoting epithelial-to-mesenchymal transition (EMT) [30,49], which in turn enables invasion and metastasis through a reduction in cellular adherence and an increase in migration. This may be partly dependent on activation of the AKT pathway, as there was a significant increase in phosphorylated AKT (Ser473) in the cells overexpressing PBX3 [49].…”
Section: Gastric Cancermentioning
confidence: 99%
“…In vitro studies have indicated a role for PBX3 in promoting epithelial-to-mesenchymal transition (EMT) [30,49], which in turn enables invasion and metastasis through a reduction in cellular adherence and an increase in migration. This may be partly dependent on activation of the AKT pathway, as there was a significant increase in phosphorylated AKT (Ser473) in the cells overexpressing PBX3 [49]. The overexpression of PBX3 also resulted in an increase in MMP9 activity [49], a key protease involved in metastasis [50], as well as an increase in the ability of gastric cancer cells to promote tubule formation by HUVEC cells, indicating an increase in pro-angiogenic signaling [49].…”
Section: Gastric Cancermentioning
confidence: 99%